Local culinary marketing training through virtual Wonderfood Sayan Village - Ni Wayan Mega Sari Apri Yani; I Wayan Putra Aditya; Bondan Pambudi; Putu Eka Wirawan; Ni Luh Putu Ayu Daniella Santika Dewi (Community Empowerment, 2022)
The Covid-19 pandemic has devastated Indonesia's tourism and creative economy industry, nearly destroying all aspects of life, particularly in Bali, which is heavily reliant on tourism. This has an impact on all aspects of society, including the citizens of Sayan Village, Gianyar, who work primarily in the hospitality and tourism industries. The purpose of the program is to provide local culinary marketing training via virtual media as an alternative to digital marketing for MSME owners to help market their products. Training, demonstration, and workshops are the methods used. The program's outcomes were successful in increasing partners' knowledge of how to market MSME products through virtual tours.